Download presentation

Presentation is loading. Please wait.

Published byCameron Stone Modified over 3 years ago

1
**A f r i d i i m r a n 94@yahoo.com**

S O L V IN G S Y ST E M S O F E Q U A T I O N S A f r i d i i m r a n

2
BY GRAPHING Y = 2X + 1 Y = -X + 4 (1,3) IS THE SOLUTION

3
**Graphing is not the only way to solve a system of equations**

Graphing is not the only way to solve a system of equations. It is not really the best way because it has to be graphed perfectly and some answers are not integers. SOOOO We need to learn another way!!!!

4
**Solve: by ELIMINATION x + y = 12 -x + 3y = -8**

Like variables must be lined under each other. Solve: by ELIMINATION x + y = 12 -x + 3y = -8 4y = 4 We need to eliminate (get rid of) a variable. The x’s will be the easiest. So, we will add the two equations. Divide by 4 y = 1 THEN----

5
**Now check our answers in both equations------**

Substitute your answer into either original equation and solve for the second variable. X +Y = 12 x + 1 = 12 x = 11 (11,1) Answer Now check our answers in both equations------

6
X + Y =12 = 12 12 = 12 -x + 3y = -8 (1) = -8 = -8 -8 = -8

7
**Solve: by ELIMINATION 5x - 4y = -21 -2x + 4y = 18**

Like variables must be lined under each other. Solve: by ELIMINATION 5x - 4y = x + 4y = 18 3x = -3 We need to eliminate (get rid of) a variable. The y’s be will the easiest.So, we will add the two equations. Divide by 3 x = -1 THEN----

8
**Now check our answers in both equations------**

Substitute your answer into either original equation and solve for the second variable. 5X - 4Y = -21 5(-1) – 4y = -21 -5 – 4y = -21 -4y = -16 y = 4 (-1, 4) Answer Now check our answers in both equations------

9
**5x - 4y = -21 5(-1) – 4(4) = -21 -5 - 16 = -21 -21 = -21**

-2(-1) + 4(4) = 18 = 18 18 = 18

10
**Solve: by ELIMINATION 2x + 7y = 31 5x - 7y = - 45**

Like variables must be lined under each other. Solve: by ELIMINATION 2x + 7y = 31 5x - 7y = - 45 7x = -14 We need to eliminate (get rid of) a variable. The y’s will be the easiest. So, we will add the two equations. Divide by 7 x = -2 THEN----

11
**Now check our answers in both equations------**

Substitute your answer into either original equation and solve for the second variable. 2X + 7Y = 31 2(-2) + 7y = 31 -4 + 7y = 31 7y = 35 y = 5 (-2, 5) Answer Now check our answers in both equations------

12
2x + 7y = 31 2(-2) + 7(5) = = = 31 5x – 7y = - 45 5(-2) - 7(5) = - 45 = - 45 - 45 =- 45

13
**Solve: by ELIMINATION x + y = 30 x + 7y = 6**

Like variables must be lined under each other. Solve: by ELIMINATION x + y = 30 x + 7y = 6 We need to eliminate (get rid of) a variable. To simply add this time will not eliminate a variable. If one of the x’s was negative, it would be eliminated when we add. So we will multiply one equation by a – 1.

14
**X + Y = 30 X + Y = 30 -X – 7Y = - 6 ( X + 7Y = 6 ) -1 -6Y = 24 - 6 - 6**

Now add the two equations and solve. - 6 - 6 Y = - 4 THEN----

15
**Now check our answers in both equations------**

Substitute your answer into either original equation and solve for the second variable. X + Y = 30 X = 30 X = 34 (34, - 4) Answer Now check our answers in both equations------

16
x + y = = = 30 x + 7y = 6 34 + 7(- 4) = 6 = 6 6 = 6

17
**Solve: by ELIMINATION x + y = 4 2x + 3y = 9**

Like variables must be lined under each other. Solve: by ELIMINATION x + y = 4 2x + 3y = 9 We need to eliminate (get rid of) a variable. To simply add this time will not eliminate a variable. If there was a –2x in the 1st equation, the x’s would be eliminated when we add. So we will multiply the 1st equation by a – 2.

18
**( ) -2 Y = 1 THEN---- X + Y = 4 -2X - 2 Y = - 8 2X + 3Y = 9**

Now add the two equations and solve. THEN----

19
**Now check our answers in both equations------**

Substitute your answer into either original equation and solve for the second variable. X + Y = 4 X + 1 = 4 X = 3 (3,1) Answer Now check our answers in both equations------

20
x + y = = = 4 2x + 3y = 9 2(3) + 3(1) = 9 6 + 3 = 9 9 = 9

Similar presentations

OK

Substitution Method: 1. Solve the following system of equations by substitution. Step 1 is already completed. Step 2:Substitute x+3 into 2 nd equation.

Substitution Method: 1. Solve the following system of equations by substitution. Step 1 is already completed. Step 2:Substitute x+3 into 2 nd equation.

© 2017 SlidePlayer.com Inc.

All rights reserved.

Ads by Google

Ppt on applied operations research analyst Ppt on patient monitoring system using gsm Ppt on introduction to 3d coordinate geometry Led based moving message display ppt on tv Ppt on conceptual art ideas Ppt on machine translation japanese Ppt on model view controller Ppt on travel and tourism in rajasthan Ppt on power diode for microwave Ppt on statistics and probability help